"Us" and "Them": Ulster Loyalist Perspectives on the IRA and Irish Republicanism. Issue 3 (26th May 2016) - McAuley, James W.; Ferguson, Neil
Abstract : This article draws on data from one-to-one interviews with members and former members of the Ulster Volunteer Force, Ulster Defence Association, Red Hand Commando, Ulster Political Research Group, and the Progressive Unionist Party to explore the dynamic and fluid perceptions of the Irish Republican Army (IRA) and Sinn Féin among Ulster loyalists. The article will explore how attitudes and perceptions are influenced by the shifting political landscape in Northern Ireland as Ulster loyalists come to terms with the new realities created by the peace process, security normalization, decommissioning, and the rise in the threat of dissident republican violence. The article will also demonstrate that these perceptions are not purely antagonistic and based on the creation of negative, stereotypical "enemy images" fuelled by decades of conflict, but pragmatic, bound to societal and local events, and influenced by intragroup attitudes and divisions, in addition to the expected conflictual ingroup vs. outgroup relationships. Finally, the article will explore how loyalists employ republicanism and the transformation of the Provisional IRA in particular, as a mirror or benchmark to reflect on their own progress since 1994.